2021
DOI: 10.2196/23313
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps for Older Adults: Systematic Search and Evaluation Within Online Stores

Abstract: Background Through the increasingly aging population, the health care system is confronted with various challenges such as expanding health care costs. To manage these challenges, mobile apps may represent a cost-effective and low-threshold approach to support older adults. Objective This systematic review aimed to evaluate the quality, characteristics, as well as privacy and security measures of mobile apps for older adults in the European commercial a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 84 publications
6
25
1
2
Order By: Relevance
“…Average user ratings in the stores showed a significantly small correlation with the MARS ratings, which is in line with that reported in previous research [ 30 , 36 ]. However, several studies (including apps for weight management and chronic pain) could not identify an association [ 29 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Average user ratings in the stores showed a significantly small correlation with the MARS ratings, which is in line with that reported in previous research [ 30 , 36 ]. However, several studies (including apps for weight management and chronic pain) could not identify an association [ 29 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…No randomized controlled trial evaluating the effectiveness of one of the included apps could be identified. This lack of a solid evidence base for the use of health apps is in line with that reported in other systematic reviews of app quality (eg, older adults, mindfulness, depression, rheumatoid arthritis, and posttraumatic stress disorder) [36][37][38][39][40]. These systematic reviews showed that the proportion of the scientifically evaluated apps ranges between 0% and 4.8%.…”
Section: Principal Findingssupporting
confidence: 79%
See 2 more Smart Citations
“…from the stores. The functionality and validity of the program has been proven in previous studies [ 44 46 ]. For further technical details please see [ 47 ].…”
Section: Methodsmentioning
confidence: 93%